2021
DOI: 10.3396/ijic.v17.20726
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perception of risk of disease, and infection prevention and control practices among healthcare workers and support staff toward COVID-19 in an Ethiopian referral hospital: a cross-sectional survey

Abstract: Coronavirus disease 2019 (COVID-19) is a pandemic affecting over 106 million and killing over 2.3 million people. Inadequate knowledge of the disease coupled with scarce or improper use of infection prevention and control (IPC) measures by healthcare workers (HCWs) and support staff may be contributing to the rapid spread of infection. This survey aims to assess knowledge, risk perception, and precaution practices of HCWs and support staff toward COVID-19 under resource-constrained circumstances at a major ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As a result, a random-effects model was used to estimate the pooled proportion of good compliance with COVID-19 preventive measures among HCWs in Ethiopia. From included studies, the highest proportion of good compliance with COVID-19 preventive measures was found to be 70% (95% CI: 65.6% to 74.4%) as reported by Mindaye et al, 56 whereas the lowest proportion of good compliance was 21.6% (95% CI: 18.5% to 24.8%) as reported by Zenbaba et al 54 To identify possible sources of heterogeneity, different factors associated with heterogeneity, such as year of publication, quality score and sample size, were investigated using a univariate meta-regression model. Unfortunately, none of the factors were identified as a significant source of heterogeneity (table 2 and figure 2).…”
Section: The Proportion Of Good Compliance With Covid-19 Preventive M...mentioning
confidence: 55%
See 1 more Smart Citation
“…As a result, a random-effects model was used to estimate the pooled proportion of good compliance with COVID-19 preventive measures among HCWs in Ethiopia. From included studies, the highest proportion of good compliance with COVID-19 preventive measures was found to be 70% (95% CI: 65.6% to 74.4%) as reported by Mindaye et al, 56 whereas the lowest proportion of good compliance was 21.6% (95% CI: 18.5% to 24.8%) as reported by Zenbaba et al 54 To identify possible sources of heterogeneity, different factors associated with heterogeneity, such as year of publication, quality score and sample size, were investigated using a univariate meta-regression model. Unfortunately, none of the factors were identified as a significant source of heterogeneity (table 2 and figure 2).…”
Section: The Proportion Of Good Compliance With Covid-19 Preventive M...mentioning
confidence: 55%
“…A total of 7933 study participants were included in the current meta-analysis to estimate the pooled proportion of good compliance with COVID-19 preventive measures among HCWs. In the present meta-analysis, six studies were from Amhara,41 53 58 59 62 65 seven studies from the Oromiya region,38 53–55 60 61 64 four from Addis Ababa,40 56 63 66 one from Southern Nations, Nationalities, and Peoples’ Region (SNNPR),39 two from Tigray region,57 67 and one study conducted in Oromiya, Amhara, Addis Ababa, Tigray, and SNNPR 42. However, none of the studies reported from Benishangul-Gumuz, Gambella and Dire Dawa regions (table 1).…”
Section: Resultsmentioning
confidence: 77%
“…One notable global challenge faced at the outset of the COVID-pandemic was that countries had limited access to consumables and physical structures relevant to breaking the transmission of SARS-CoV-2 in a health-care setting. 26 A critical note by Patel et al, 27 might further suffice the argument, that in developing countries access to clean water and hand rub alcohol are self-limiting to HCWs to practice hand hygiene and other IPC practices. By far, most papers reviewed, 20,28,29 strengthen this claim, however, the readiness of facilities in terms of access to water and disinfectant was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when designing and conducting IPC training, considering the audience can enhance the effectiveness of the training. According to Patel et al, 27 during the onset of the pandemic, training provided to developing countries, under the WHO guidance for infection prevention and emergency response was primarily directed, for instance in Ethiopia to only accommodate 4293 clinical practitioners, which has excluded the nonclinical workforce. It seems related to these shortcomings, that there is a wider gap in effective compliance with IPC practices among porters, runners, and hospital cleaners of health facilities in Addis Ababa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation